Towards a historical archive of Alianza Lima: The role of collectors - Vich, Víctor (2025)
This paper highlights the value of collectors in the reconstruction of the history of Peruvian sports and, in this case, of a soccer team. It is affirmed, on the one hand, that a collection fulfills a function similar to that of a documentary archive and, on the other hand, that it possesses heterodox and unpublished sources for the reconstruction of history. The essay discusses and showcases the work of four collectors in Peru. The description of their collections is parallel to theoretical counterpoints in order to show new ways to investigate the past.